2022
DOI: 10.1038/s42003-022-03510-w
|View full text |Cite
|
Sign up to set email alerts
|

Gametocyte-specific and all-blood-stage transmission-blocking chemotypes discovered from high throughput screening on Plasmodium falciparum gametocytes

Abstract: Blocking Plasmodium falciparum human-to-mosquito transmission is essential for malaria elimination, nonetheless drugs killing the pathogenic asexual stages are generally inactive on the parasite transmissible stages, the gametocytes. Due to technical and biological limitations in high throughput screening of non-proliferative stages, the search for gametocyte-killing molecules so far tested one tenth the number of compounds screened on asexual stages. Here we overcome these limitations and rapidly screened aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The analysis revealed an enrichment of; Pf3D7_0904900 (Cu 2+ ATPase), Pf3D7_1352100 (Mdr6), Pf3D7_1303500 (Nhe-1), Pf3D7_1235200 (Vp2), and Pf3D7_0830500 highlighting an active interaction with transmembrane solute transporters of both monovalent and divalent cations, as well as amino acids trafficking. Previous studies have demonstrated that solute carrier inhibitors are potent gametocytocidal [ 22 , 30 , 41 ]. As high expression of membrane enriched proteins was reported in late-stage gametocytes [ 88 ], and going by the fact that these aforementioned compounds target membrane ion transporters, our data, therefore, support the argument that late-stage gametocytes are likely permeable to ionic homeostasis disruptors.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis revealed an enrichment of; Pf3D7_0904900 (Cu 2+ ATPase), Pf3D7_1352100 (Mdr6), Pf3D7_1303500 (Nhe-1), Pf3D7_1235200 (Vp2), and Pf3D7_0830500 highlighting an active interaction with transmembrane solute transporters of both monovalent and divalent cations, as well as amino acids trafficking. Previous studies have demonstrated that solute carrier inhibitors are potent gametocytocidal [ 22 , 30 , 41 ]. As high expression of membrane enriched proteins was reported in late-stage gametocytes [ 88 ], and going by the fact that these aforementioned compounds target membrane ion transporters, our data, therefore, support the argument that late-stage gametocytes are likely permeable to ionic homeostasis disruptors.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to find a neutral locus for transgene insertion into P. falciparum genome, we initially selected the cg6 locus, which has been shown to be dispensable for asexual and gametocyte parasite development in vitro and has been previously used as a docking site (34,35). However, we found out that disruption of cg6 caused a significant reduction in oocyst loads (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Luminescence from expressed luciferase has been used as a readout for drug assays against P. falciparum at multiple life cycle stages 17 , 26 31 . Although HTS for gametocytocidal drugs, which utilises luciferase-expressing P. falciparum , was recently achieved by a relatively robust and simple assay method, the reporter line has not been optimised for assays targeting asexual blood- and liver-stage parasites because luciferase expression is confined to the gametocyte stage 32 .…”
Section: Introductionmentioning
confidence: 99%